2021
DOI: 10.3390/foods10102461
|View full text |Cite
|
Sign up to set email alerts
|

Baking Quality Assessment of Twenty Whole Grain Oat Cultivar Samples

Abstract: Whole grain oat has become an increasingly popular baking ingredient. Still, oat baking poses many industrial challenges because the baking quality criteria have not been set for whole grain oat flours, and cultivar variation remains unknown. We aimed to assess the baking quality variation of twenty whole grain oat cultivar samples, and to identify the factors that caused the variation. It was hypothesised that by optimising the water absorption of the dough (i.e., dough yield) by test baking method, the best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…However, the bioaccessibility of folate in LOC was high with 102% ± 11%. Data about the baking quality of LOA, LOB and LOC has been reported by Sammalisto et al (referred to F16, F25, F19 respectively), 36 and LOC had the lowest crumb hardness value. Low bioaccessibility of folate in oat bread compared to the other breads could be linked to the existence of beta-glucan, which can slow down the in vitro digestion of starch by hindering the efficiency of amylase.…”
Section: Papermentioning
confidence: 85%
“…However, the bioaccessibility of folate in LOC was high with 102% ± 11%. Data about the baking quality of LOA, LOB and LOC has been reported by Sammalisto et al (referred to F16, F25, F19 respectively), 36 and LOC had the lowest crumb hardness value. Low bioaccessibility of folate in oat bread compared to the other breads could be linked to the existence of beta-glucan, which can slow down the in vitro digestion of starch by hindering the efficiency of amylase.…”
Section: Papermentioning
confidence: 85%
“…16,25 Meanwhile, OSDF was almost made up of Glc (96.61%) with a few Ara (1.01%) and Xyl (2.38%), suggesting a kind of glucan. 26 Compared with the three SDFs, the rest had a more balanced monosaccharide composition, where no sugar had a proportion of more than 40%. KSDF was characterized by a high proportion of Man (36.4%) and also contained 26.80% Gal, 18.50% Ara, 9.04% Glc, 4.52% GalA, 3.67% Rha, and 1.08% Xyl.…”
Section: Resultsmentioning
confidence: 95%
“…As the physicochemical properties differ between oat cultivar samples, presumably the milling properties vary as well. A further study showed that in the set of 20 oat cultivar samples, oat flour particle size parameters (average particle size D 4,3 and median particle size D 50 ) were related to the baking quality of whole grain oat flours (Sammalisto et al, 2021). Regarding oat flakes, it has been reported that oat cultivar samples varied in the oat flake properties (Jokinen et al, 2022;Lapveteläinen et al, 2001), oat flake granulation and oatmeal texture (Rhymer et al, 2005).…”
Section: Introductionmentioning
confidence: 94%